Analisis Pengaruh Kualitas Website Terhadap Kepuasan Pengguna Berdasarkan Metode Webqual 4.0 Pada Universitas Narotama - Wawolumaya, Edelwy Apriliana; Sunarto, Dewi yani; Wulandari, Sri Hariani Eko (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Website is one source of information that is essential, including in college, for that reason important held management website. Narotama University is one of private university based technology in east java, has a website www.narotama.ac.id. Until now has never been evaluation on the quality website of Narotama University. To measure the website quality of Narotama University, has been done with analyzing influence of Information Quality , Interaction , and website used towards User Satisfaction . Analyzing the website quality has been done through several stages such as collecting the data by interviewing some sources and did an observations as well. Furthermore, analyzing by using webqual method through preparing questionnaire based on the dimension of webqual. The phase of this analysis is using Multiple Linear Regression. Meanwhile, the prerequisite test has been done to test the validity, reliability, assumptions and testing the regression coefficients at the same time and partial. The result of these tests showed that the variable of quality information has a positive and significant effect toward users’ satisfaction. However, there are still needs an evaluation and improvement based on an indicators of webqual.